Work Environments : Spatial concepts, Usage strategies, Communications - Schittich, Christian editor 385213 (Munich : Edition Detail ; Basel : Birkhũser, 2011)
The requirements confronting our workplaces have recently undergone a dramatic transformation. Constantly shifting workspace populations and varying uses of workspace call for flexible spatial structures, and so do new professions and innovative working methods. The planning of workspaces is influenced by the digitalization of our storage media as well as by new materials and building technologies. And yet for all the importance of flexibility and technology, the ultimate focus is still on human beings. How, then, can the multilayered concepts of indoor climate, lighting, acoustics, and ergonomics be reconciled with spatial structures that lend themselves to a wide variety of uses? In keeping with the typological approach of the series, this volume of the series In DETAIL presents the various working environments organized according to use. The focus throughout is on the successful interplay between technical standards, organizational structures, and human needs.